An on-line study about consumers' perception and purchasing behavior toward umami seasonings in China. (April 2020) - Zhu, Yiwen; Chen, Yan Ping; Ayed, Charfedinne; Li, Bei; Liu, Yuan
Abstract: Though umami seasonings (UMS) play an important part in food flavor and supply in Asian cuisine, little is known about consumers' thoughts and willingness to pay for UMS in China. Thus, this study gives a first insight into Chinese consumers' knowledge, purchasing behavior and willingness to pay for UMS and explores the deciding factors related to the acceptance of UMS. An online consumer survey containing 29 questions was conducted, and 2839 Chinese people participated in the survey. It was concluded that consumers had a general concept of UMS, but they did not have enough knowledge about it. A total of 62.6% respondents thought the intake of UMS at an appropriate amount did not have negative impacts on health. Respondents preferred to buy UMS from supermarkets and get information from television, friends/relatives and the internet. About two-thirds of respondents (63.8%) would consider to purchase more UMS once specialized institutes could provide to consumers scientifically validated information regarding UMS. This study may help the global seasoning market to come up with seasoning products that resonate with consumers. Highlights: Online survey on umami seasonings (UMS) taken by 2839 Chinese consumers was conducted. Chinese consumers had a high awareness but misguided knowledge about UMS. The willing to pay would increase based on extensive education and popularization of science.